Designing a CEFR B1-Based Arabic Speaking Assessment Prototype Through the Adaptation of Ali Al-Khuli’s Speaking Task Framework - Siti Nurfadlilah; Ihwan Mahmudi; Aisyah Dwi Sena Daundi; Risti Nur Juniarti; Nurhidayah Binti Mohd Noor (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2026)
Although the Common European Framework of Reference for Languages (CEFR) has become an international standard for language assessment, standardized CEFR-based Arabic speaking assessment instruments remain limited, particularly those that operationalize the CEFR Companion Volume descriptors into authentic communicative tasks. This study aimed to develop a prototype of a CEFR B1-based Arabic speaking assessment by integrating Ali Al-Khuli’s speaking task framework with the CEFR Companion Volume descriptors. Employing a Design and Development Research approach, the study involved document analysis of CEFR descriptors and relevant literature on Arabic language assessment. The development process comprised needs analysis, descriptor mapping, assessment blueprint design, task adaptation, rubric development, and prototype construction. The resulting prototype consists of fifteen authentic communicative speaking tasks systematically aligned with CEFR B1 descriptors and an analytic scoring rubric encompassing pronunciation, vocabulary, grammatical accuracy, fluency, interaction, coherence, content relevance, and delivery. The prototype emphasizes communicative performance through contextualized speaking activities and multidimensional assessment criteria, providing a more comprehensive framework than conventional grammar-oriented speaking tests. Although empirical validation and psychometric evaluation were beyond the scope of this study, the proposed prototype establishes a theoretically grounded foundation for future validation. It contributes to the development of standardized, transparent, and internationally aligned Arabic-speaking assessment practices.